ANALISIS LINGKUNGAN STRATEGIK DI LEMBAGA PENDIDIKAN ISLAM - Syamrina, Syamrina; Mar’ah, Khaeratul; Idris, Ridwan (Department of Islamic Education Management, 2026)
This study aims to analyze the strategic environment of Islamic educational institutions by examining internal and external factors that influence the direction of institutional development. This research employs a literature review method by gathering relevant sources such as journals, scholarly articles, books, and other academic documents. The data were analyzed descriptively through processes of reduction, categorization, and interpretation of information related to strategic environmental management. The findings reveal that strategic environmental analysis plays an essential role in helping Islamic educational institutions identify internal strengths and weaknesses, as well as recognize external opportunities and threats. Furthermore, the study indicates that factors such as human resources, learning technology, educational policies, and socio-cultural developments significantly affect the sustainability and competitiveness of these institutions. The study concludes that strategic environmental analysis serves as a fundamental basis for planning and decision-making within Islamic educational institutions. Its implications suggest that institutions need to conduct periodic environmental evaluations and develop adaptive strategies to effectively respond to increasingly complex environmental changes.